Mallarmé devant ses contemporains - S. Hambly, Peter (University of Adelaide Press, 2011)
The enigmatic nature of Mallarmé's works disconcerted his first readers and they were published at a period when the number of newspaper and periodicals was rapidly increasing. In the last quarter of the 19th century many comments on his writings appeared in print, some were laudatory, others claimed that he wished to found a poetic School of the Unintelligible. Today's reader will find gathered here reviews published when individual works first appeared and critical texts on his work in general. Among the aspects of his influence on his contemporaries which have been little known hitherto are the reactions of those who heard the first performances of Debussy's Prelude to the Afternoon of a Faun in 1894 and 1895, and the use that was made of Mallarmé's name in aesthetic and political polemics at the time, associating him with Odilon Redon or Émile Zola. Some of his utterances made at the celebrated Mardis are also recorded here.